Electrolyte for ternary lithium ion battery and lithium ion battery
By adjusting the solvent composition in the electrolyte of the lithium-ion battery, increasing the ratio of cyclic and linear carbonate, and adding fluorocarboxylate and halogenated nitrile, the performance problems of lithium-ion batteries at low and high temperatures are solved, and the efficient operation and long life of the battery in a wide temperature range is achieved.
Patent Information
- Application Number
- CN202510075317.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Existing lithium-ion batteries have large impedance and are easy to solidify at low temperatures, which makes the battery difficult to charge and discharge, and are easy to dissociate lithium; at high temperatures, the electrolyte decomposes and volatility intensifies, and the interface mask is unstable, resulting in a short battery cycle life.
An electrolyte that takes into account both low and high temperature properties, including lithium salts, solvents and film-forming additives. The ratio of cyclic carbonate and linear carbonate is increased to the solvent, especially the combination of diethyl carbonate and dimethyl carbonate, to increase the low-temperature working range of the electrolyte. At the same time, fluorocarboxylic acid ester and halogenated nitrile are added as solvents to improve conductivity and high temperature stability.
The electrolyte exhibits good electrical performance at -40℃ and 60℃, with high low-temperature discharge capacity and efficiency, and the high-temperature cycle capacity retention rate also reaches more than 75%, significantly extending the cycle life of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte for a ternary lithium ion battery and a lithium ion battery. Background Art
[0002] How to utilize and store clean energy that replaces traditional energy is crucial. Various clean energy sources often need to be converted into electricity to be used more conveniently, so the storage of electricity is particularly important. Batteries, as an important carrier for storing electricity, play a key role. Based on this, the development of battery technology is very necessary. Lithium batteries have become the preferred choice for many battery application fields due to their high energy density and long life, such as electric vehicles, digital products, energy storage equipment, etc. It is very important to broaden the use environment of lithium batteries, such as broadening the upper and lower operating temperatures of the battery, increasing the operating voltage, and the upper current limit to meet the needs of more users. Among the various component materials of lithium battery cells (such as positive electrodes, negative electrodes, electrolytes, etc.), electrolytes have a great limiting effect on the working conditions of lithium batteries, so the necessity of developing new electrolytes with high tolerance is obvious.
[0003] For lithium batteries, both low-temperature and high-temperature working conditions face different problems and challenges. At low temperatures, all materials inside lithium batteries face deterioration in power performance, resulting in increased battery impedance, difficulty in battery charging and discharging, difficulty in exerting capacity, and easy lithium precipitation during use, causing safety hazards; and most of the power problems of battery materials at low temperatures are related to the electrolyte, such as the conductivity of the electrolyte itself, the resistance encountered when lithium ions separate from the solvent from the liquid electrolyte and enter the solid electrode, and the impedance of the solid-liquid interface film generated by the electrolyte on the surface of the electrode material. In addition, at extremely low temperatures, the electrolyte also faces the problem of solvent component solidification causing electrolyte failure. At high temperatures, the battery faces problems such as electrolyte decomposition, increased volatilization, and unstable interface films, resulting in loss of electrode materials, increased gas production, and accelerated battery degradation.
[0004] Patent CN116632347A adds sulfur-containing additives to the electrolyte to form a thin and flexible SEI film rich in sulfur on the surface of the silicon-based negative electrode, thereby improving the high-temperature stability of the battery. However, the high-temperature stability of the electrolyte solvent system and the lithium salt itself, as well as the high-temperature stability of the solid-liquid contact interface on the surface of the electrode material, have an important influence on the high-temperature cycle performance of the battery, and the high-temperature cycle capacity retention rate of the disclosed technical solution is relatively poor. Summary of the invention
[0005] In view of the shortcomings of conventional electrolytes, such as large impedance and easy solidification at low temperatures, difficulty in battery charging and discharging, and easy lithium precipitation; at high temperatures, the electrolyte decomposition and volatilization intensify, the interface film is unstable, resulting in a short battery cycle life, etc., the purpose of the present invention is to provide an electrolyte for ternary lithium-ion batteries that has both low-temperature and high-temperature performance; another purpose of the present invention is to provide a lithium-ion battery with good low-temperature and high-temperature cycle performance.
[0006] The invention discloses an electrolyte for a ternary lithium-ion battery, comprising a lithium salt, a solvent and a film-forming additive; the solvent comprises a cyclic carbonate, a linear carbonate and a carboxylate; the mass of the cyclic carbonate accounts for 20-35% of the mass of the solvent, the mass of the linear carbonate accounts for 50-70% of the mass of the solvent, and the mass of the carboxylate accounts for 5-20% of the mass of the solvent; the linear carbonate comprises a combination of diethyl carbonate (DEC) and dimethyl carbonate (DEC).
[0007] At low temperatures (such as -40°C), the biggest problem facing conventional electrolytes is the precipitation of high melting point solvent components (such as ethylene carbonate) and the significant increase in viscosity when approaching precipitation. Increasing the proportion of low melting point and low viscosity components (such as diethyl carbonate and dimethyl carbonate) in the solvent can effectively expand the low temperature working range of the electrolyte.
[0008] Furthermore, in the solvent, the mass ratio of the diethyl carbonate to the dimethyl carbonate is 1-5:1.
[0009] Furthermore, in the solvent, the mass fractions of the diethyl carbonate and the dimethyl carbonate are both 30%.
[0010] Further, the cyclic carbonate includes any one of ethylene carbonate (EC), propylene carbonate (PC) and fluoroethylene carbonate (FEC) or a combination of at least two thereof.
[0011] Further, the carboxylic acid ester includes any one of ethyl acetate (EA), methyl difluoroacetate (DFMA), ethyl difluoroacetate (DFEA), methyl trifluoroacetate (TFMA), ethyl trifluoroacetate (TFEA), or a combination of at least two thereof.
[0012] Furthermore, the carboxylate is a fluorocarboxylate, and the fluorocarboxylate includes any one of methyl difluoroacetate (DFMA), ethyl difluoroacetate (DFEA), methyl trifluoroacetate (TFMA), ethyl trifluoroacetate (TFEA), or a combination of at least two thereof.
[0013] As a solvent for the electrolyte, fluorocarboxylic acid esters have the advantages of low viscosity, good negative electrode compatibility and high temperature stability, and have performance in a wide temperature range.
[0014] Furthermore, the solvent further comprises halogenated nitrile; the mass of the halogenated nitrile accounts for 1-20% of the mass of the solvent.
[0015] Further, the halogenated nitrile includes any one of fluoroacetonitrile (FAN), difluoropropionitrile, trifluoropropionitrile, chloroacetonitrile, dichloroacetonitrile, trichloroacetonitrile, bromoacetonitrile, and dibromoacetonitrile, or a combination of at least two thereof.
[0016] The small molecule solvent acetonitrile has a very low viscosity and a high dielectric constant, which can improve the conductivity, but it will react with the negative electrode; while its fluorinated product fluoroacetonitrile is compatible with the negative electrode, has a low viscosity and a higher boiling point, and can also change the lithium ion solvation structure to form a lithium ion rapid transmission channel, thus combining the advantages of a wide temperature range and high rate.
[0017] Furthermore, the lithium salt includes any one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate and lithium hexafluoroarsenate, or a combination of at least two thereof; and the concentration of the lithium salt in the solvent is 0.8-1.3 mol / L.
[0018] Furthermore, the lithium salt comprises a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, wherein the concentration of lithium hexafluorophosphate is 0.4-0.6 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide is 0.4-0.7 mol / L.
[0019] The thermal stability of lithium hexafluorophosphate in conventional electrolytes is poor, while lithium imide salts have better thermal stability and power performance. The lithium source uses a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, which simultaneously improves the high and low temperature performance of the electrolyte.
[0020] Furthermore, the film-forming additive includes dithiothreitol (DTD), and the mass of the film-forming additive accounts for 0.2-3% of the mass of the electrolyte.
[0021] Adding film-forming additives such as vinyl sulfate to the electrolyte can form a stable interface film between the positive and negative electrodes, reduce electrolyte decomposition, and improve cycle performance.
[0022] The present invention also discloses a lithium-ion battery, comprising a positive electrode sheet having a ternary positive electrode active material, a separator, a negative electrode sheet and the electrolyte as described above.
[0023] The lithium ion battery has a discharge capacity of more than 160 mAh / g at -40°C and a discharge efficiency of more than 76%; a discharge capacity of more than 156 mAh / g at the 200th cycle at 60°C and a capacity retention rate of more than 75% at the 200th cycle.
[0024] The negative electrode plate includes a negative electrode active material, and the negative electrode active material is one or more of synthetic graphite, natural graphite, soft carbon, hard carbon, silicon, silicon carbon and silicon oxygen.
[0025] The diaphragm is one or more of a PP diaphragm, a PE diaphragm, a PE / PP double-layer composite membrane, a PI electrostatic spinning diaphragm, a PP / PE / PP three-layer composite membrane, a ceramic diaphragm and a PVDF coated diaphragm.
[0026] The invention discloses an electrolyte for a ternary lithium-ion battery. The addition amounts of cyclic carbonate and linear carbonate are regulated, and the linear carbonate adopts a combination of diethyl carbonate and dimethyl carbonate, which can effectively reduce the melting point and viscosity of the electrolyte system, thereby effectively widening the low-temperature working range of the electrolyte, so that the electrolyte has good electrical properties at both high and low temperatures. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] Example 1
[0029] 1. Preparation of electrolyte:
[0030] Lithium salts: lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the concentrations of which in the solvent are both 0.5 mol / L.
[0031] Solvent: 10% EC, 10% PC, 5% FEC, 15% EA, 30% DMC and 30% DEC by mass.
[0032] Film-forming additive: DTD with a mass fraction of 1% in the total electrolyte.
[0033] Control the moisture content in the glove box to be less than 10ppm, and control the moisture content of the solvent to be less than 10ppm. Use a pipette to accurately transfer different solvents in the glove box according to a certain ratio, transfer them to an aluminum bottle, stir them thoroughly, and then store them in a constant temperature box at 0℃ for 1 hour. Then add lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide to the mixed solvent at a concentration of 0.5mol / L, stirring while adding.
[0034] 2. Assemble lithium-ion batteries (including positive electrode, negative electrode, separator and electrolyte)
[0035] Positive electrode: The positive electrode active material is the ternary positive electrode material LiNi 0.8 Mn 0.1 Co 0.1O2. The positive electrode active material, conductive agent, and binder polyvinylidene fluoride (PVDF) are dispersed in N-methylpyrrolidone with a mass ratio of 97:1.5:1.5, and then fully stirred according to the homogenization process. The uniformly dispersed positive electrode slurry is evenly coated on aluminum foil, and the positive electrode sheet is obtained after baking, rolling, slitting, and punching.
[0036] Negative electrode: The negative electrode active material is natural graphite. Natural graphite, conductive agent, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) are put into a planetary stirring tank at a mass ratio of 96:1:2:1, and a uniformly dispersed negative electrode slurry is prepared according to the slurry making process. The negative electrode slurry is then evenly coated on the copper foil, and after baking, rolling, slitting, and punching, the negative electrode sheet is obtained.
[0037] Diaphragm: PP diaphragm.
[0038] After the positive and negative electrodes are punched, the positive electrode is placed in an oven at 130°C, and the negative electrode is placed in an oven at 100°C for 25 hours. When the moisture content of the electrode meets the requirements, the positive electrode, negative electrode and diaphragm are placed in a stacking machine to stack into bare cells, which are then packaged into stamped aluminum-plastic film bags. After the packaged dry cells are dried at 90°C for 11 hours, the prepared electrolyte is injected into the dry cells. After the cells are shelved, formed, shelved at high temperature, evacuated and sealed, and capacity divided, lithium-ion batteries are obtained.
[0039] Example 2
[0040] The difference from Example 1 is that the mass fractions of 30% DMC and 30% DEC in the electrolyte solvent are replaced by 10% DMC and 50% DEC.
[0041] Example 3
[0042] The difference from Example 1 is that the mass fractions of 30% DMC and 30% DEC in the solvent of the electrolyte are replaced by 50% DMC and 10% DEC.
[0043] Example 4
[0044] The difference from Example 1 is that 15% by mass of EA in the solvent of the electrolyte is replaced by an equal amount of DFEA.
[0045] Example 5
[0046] The difference from Example 1 is that 15% by mass of EA in the solvent of the electrolyte is replaced by an equal amount of FAN.
[0047] Example 6
[0048] The difference from Example 1 is that 15% by mass of EA in the solvent of the electrolyte is replaced by 7.5% by mass of DFEA and 7.5% by mass of FAN.
[0049] Comparative Example 1
[0050] The difference from Example 1 is the composition of the electrolyte:
[0051] Lithium salts: lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, the concentrations of which in the solvent are both 0.5 mol / L.
[0052] Solvent: 10% EC, 10% PC, 5% FEC, 15% EA and 60% EMC by mass.
[0053] Film-forming additive: DTD with a mass fraction of 1% in the total electrolyte.
[0054] Comparative Example 2
[0055] The difference from Comparative Example 1 is that 15% EA and 60% EMC in the solvent of the electrolyte are replaced by 75% EMC, the lithium salt is 1.0 mol / L lithium hexafluorophosphate, does not contain lithium bis(fluorosulfonyl)imide, and no DTD is added.
[0056] Comparative Example 3
[0057] The difference from Comparative Example 1 is that 15% of EA and 60% of EMC in the solvent of the electrolyte are replaced by 75% of EMC, the lithium salt is 1.0 mol / L lithium hexafluorophosphate, and does not contain lithium bis(fluorosulfonyl)imide.
[0058] Comparative Example 4
[0059] The difference from Comparative Example 1 is that 15% of EA and 60% of EMC in the solvent of the electrolyte are replaced by 75% of EMC.
[0060] Performance Test:
[0061] The lithium-ion batteries assembled in the examples and comparative examples were tested using the following method to compare the performance differences:
[0062] (1) Electrolyte conductivity test
[0063] The electrolytes in the embodiments and comparative examples were tested for room temperature conductivity using a conductivity tester. Specific test data are shown in Table 1.
[0064] (2) Lithium-ion battery discharge test at room temperature and low temperature
[0065] The batteries of the examples and comparative examples were subjected to normal temperature and low temperature discharge tests according to the following steps. The detailed steps were as follows: Take the lithium-ion battery after constant volume and leave it standing for more than 1 h. Then, charge it at a constant current and constant voltage at C / 3 at normal temperature, with a cut-off voltage of 4.25 V and a cut-off current of 0.05C. Then, discharge it at a constant current of C / 5 at 25 °C or -40 °C until the voltage reaches 2.8 V to obtain the discharge capacity at 25 °C or -40 °C. The specific test data are shown in Table 2.
[0066] (3) High temperature cycle test of lithium-ion battery
[0067] The batteries of the examples and comparative examples were subjected to high temperature cycle tests according to the following steps. The detailed steps were as follows: Take the lithium-ion battery after constant volume and leave it standing for more than 1 h. Then, at 60 °C, charge it at a constant current and constant voltage at 1C, with a cut-off voltage of 4.25 V and a cut-off current of 0.05C, and then discharge it at a constant current of 1C until the voltage reaches 2.8 V. Charge and discharge the battery in cycles according to the above steps, and record the discharge capacity of the first cycle, the discharge capacity after 200 cycles, and the capacity retention rate. The specific test data are shown in Table 3.
[0068] Table 1 Test results of conductivity
[0069] Group Conductivity (mS / cm) Example 1 10.14 Example 2 9.89 Example 3 10.34 Example 4 9.94 Example 5 10.65 Example 6 10.31 Comparative Example 1 10.12 Comparative Example 2 8.43 Comparative Example 3 8.40 Comparative Example 4 8.42
[0070] As shown in Table 1, the conductivities of Examples 1-6 and Comparative Example 1 are all higher than those of Comparative Examples 2-4. It can be seen that adding carboxylic ester, fluorinated carboxylic ester or halogenated nitrile to the solvent of the electrolyte can effectively reduce the viscosity of the electrolyte system, thereby increasing the conductivity of the electrolyte. In Examples 1-3, when the total amount of DMC and DEC is fixed, as the content of DMC increases, the conductivity increases accordingly. It can be seen that DMC can also reduce the viscosity and increase the conductivity. In Examples 1, 4, and 5, when other components in the electrolyte remain unchanged and the same mass fraction of EA, DFEA, and FAN are added, the conductivity is DFEA < EA < FAN. It can be seen that the order of the improvement effect on conductivity is halogenated nitrile > carboxylic ester > fluorinated carboxylic ester.
[0071] Table 2 Test results of normal temperature and low temperature discharge
[0072] Group Discharge capacity at room temperature (C / 5) Low temperature discharge capacity (C / 5) Low temperature discharge efficiency Example 1 209.6 166.4 79.4% Example 2 209.4 162.5 77.6% Example 3 209.5 160.9 76.8% Example 4 209.0 165.1 79.0% Example 5 209.8 182.3 86.9% Example 6 209.5 174.1 83.1% Comparative Example 1 209.1 144.7 69.2% Comparative Example 2 208.7 101.8 48.8% Comparative Example 3 208.9 102.6 49.1% Comparative Example 4 208.8 117.6 56.3%
[0073] As shown in Table 2, the room temperature discharge capacity of all embodiments and comparative examples is 209 mAh / g, with small differences. At -40°C, the low temperature discharge capacity and low temperature discharge efficiency (i.e., the proportion of low temperature discharge capacity to room temperature discharge capacity) of comparative example 4 are higher than those of comparative examples 2 and 3. Compared with lithium hexafluorophosphate, lithium bisfluorosulfonyl imide has better power performance. The combination of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide can improve the low temperature performance of the battery. The low temperature discharge capacity and low temperature discharge efficiency of Examples 1-6 and Comparative Example 1 are higher than those of Comparative Example 4. Adding carboxylic acid esters / fluorocarboxylic acid esters or halogenated nitrile to the solvent can effectively improve the low temperature discharge performance, which is mainly due to the improvement of the conductivity of the electrolyte. The low temperature discharge capacity and low temperature discharge efficiency of Examples 1-3 are higher than those of Comparative Example 1. When the mixed solvent of DMC and DEC replaces EMC in equal amounts, DMC can reduce the viscosity, and DEC can reduce the melting point of the electrolyte, so that the conductivity of the electrolyte is improved at extremely low temperatures, thereby improving the low temperature discharge efficiency. The low-temperature discharge capacity and low-temperature discharge efficiency of Examples 2 and 3 are lower than those of Comparative Example 1. It can be seen that at extremely low temperatures, when DMC is too little, the viscosity of the electrolyte decreases, and when DEC is too little, the melting point of the electrolyte increases. Both have a deteriorating effect on the conductivity and reduce the low-temperature discharge efficiency. In Examples 1, 4, and 5, when the other components in the electrolyte remain unchanged and the same mass fraction of EA, DFEA, and FAN are added, the low-temperature discharge efficiencies of DFEA and EA are similar, and FAN significantly improves the low-temperature discharge efficiency. Fluoroacetonitrile not only has low viscosity, but also can change the lithium ion solvation structure and form a lithium ion fast transmission channel, thereby significantly improving the low-temperature performance. In Example 6, the same amount of DFEA and FAN is added compared to Examples 4 and 5, and the low-temperature discharge efficiency is between Examples 4 and 5.
[0074] Table 3 High temperature cycle test results
[0075]
[0076] As shown in Table 3, the first cycle capacity of high-temperature discharge of all embodiments and comparative examples is about 205-206 mAh / g, with little difference. The capacity retention rate of 200 cycles of high-temperature cycle in Comparative Example 3 is higher than that in Comparative Example 2. The additive vinyl sulfate can form a stable interface film at the positive and negative electrodes, reduce the decomposition of the electrolyte, and improve the cycle performance. Compared with Comparative Example 3, the high-temperature cycle capacity retention rate of Comparative Example 4 is further improved. Lithium bis(fluorosulfonyl)imide has better thermal stability than lithium hexafluorophosphate, which can improve the high-temperature performance of the battery. The high-temperature cycle capacity retention rate of Comparative Example 1 is lower than that of Comparative Example 4. The low-chain carboxylic acid ester has a low boiling point, is easy to volatilize and produce gas at high temperature, and has poor compatibility with graphite-based negative electrodes. It is easy to decompose and produce gas on the surface of the negative electrode at high temperature, and has poor high-temperature cycle performance. The capacity retention rate of 200 cycles of high-temperature cycle in Examples 1-3 is higher than that in Comparative Example 1. When the mixed solvent of DMC and DEC replaces EMC in equal amounts, DEC can increase the boiling point and reduce high-temperature gas production. DMC helps to improve the film formation stability, thereby improving the high-temperature cycle performance. However, when the DMC content is high, such as in Example 3, the high-temperature cycle retention rate decreases. When the DMC content is too high, the boiling point of the solvent decreases, the high-temperature gas production increases, and the high-temperature cycle performance decreases. In Examples 1, 4, and 5, when the other components in the electrolyte remain unchanged and the same mass fraction of EA, DFEA, and FAN are added, the high-temperature cycle capacity retention rates of FAN and EA are similar, and DFEA significantly improves the high-temperature cycle capacity retention rate. Compared with ordinary carboxylates, fluorocarboxylates have better thermal stability and improved high-temperature cycle performance. Compared with Examples 4 and 5, Example 7 adds equal amounts of DFEA and FAN, and the high-temperature cycle capacity retention rate is between Examples 4 and 5.
[0077] Combining Table 2 and Table 3, Example 5 has the best low temperature performance when FAN is added alone, Example 4 has the best high temperature performance when DFEA is added alone, and Example 6 has excellent high and low temperature performance when equal amounts of FAN and DFEA are added at the same time, while the high conductivity of the halogenated nitrile and the high temperature stability of the fluorocarboxylic acid ester are brought into play at the same time.
[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An electrolyte for a ternary lithium-ion battery, characterized in that: The invention comprises a lithium salt, a solvent and a film-forming additive; the solvent comprises a cyclic carbonate, a linear carbonate and a carboxylate; the mass of the cyclic carbonate accounts for 20-35% of the mass of the solvent, the mass of the linear carbonate accounts for 50-70% of the mass of the solvent, and the mass of the carboxylate accounts for 5-20% of the mass of the solvent; the linear carbonate comprises a combination of diethyl carbonate and dimethyl carbonate.
2. The electrolyte for a ternary lithium-ion battery according to claim 1, characterized in that: The cyclic carbonate includes any one of ethylene carbonate, propylene carbonate and fluoroethylene carbonate, or a combination of at least two thereof.
3. The electrolyte for a ternary lithium-ion battery according to claim 1, characterized in that: The carboxylic acid ester includes any one of ethyl acetate, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroacetate, and ethyl trifluoroacetate, or a combination of at least two thereof.
4. The electrolyte for a ternary lithium-ion battery according to claim 3, characterized in that: The carboxylate is a fluorinated carboxylate, and the fluorinated carboxylate includes any one of methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroacetate, and ethyl trifluoroacetate, or a combination of at least two thereof.
5. The electrolyte for a ternary lithium-ion battery according to claim 1, characterized in that: The solvent further comprises halogen nitrile; the mass of the halogen nitrile accounts for 1-20% of the mass of the solvent.
6. The electrolyte for a ternary lithium-ion battery according to claim 5, characterized in that: The halogenated nitrile includes any one of fluoroacetonitrile, difluoropropionitrile, trifluoropropionitrile, chloroacetonitrile, dichloroacetonitrile, trichloroacetonitrile, bromoacetonitrile and dibromoacetonitrile, or a combination of at least two thereof.
7. The electrolyte for a ternary lithium-ion battery according to claim 1, characterized in that: The lithium salt includes any one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate and lithium hexafluoroarsenate, or a combination of at least two thereof; the concentration of the lithium salt in the solvent is 0.8-1.3 mol / L.
8. The electrolyte for a ternary lithium-ion battery according to claim 7, characterized in that: The lithium salt comprises a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, wherein the concentration of the lithium hexafluorophosphate is 0.4-0.6 mol / L, and the concentration of the lithium bis(fluorosulfonyl)imide is 0.4-0.7 mol / L.
9. The electrolyte for a ternary lithium-ion battery according to claim 1, characterized in that: The film-forming additive comprises vinyl sulfate, and the mass of the film-forming additive accounts for 0.2-3% of the mass of the electrolyte.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet having a ternary positive electrode active material, a separator, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 9.